Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0006-3495(00)76359-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Oligomeric States of Insulin in Self-Assembly and Amyloid Fibril Formation by Mass Spectrometry

Abstract: The self-assembly and aggregation of insulin molecules has been investigated by means of nanoflow electrospray mass spectrometry. Hexamers of insulin containing predominantly two, but up to four, Zn(2+) ions were observed in the gas phase when solutions at pH 4.0 were examined. At pH 3.3, in the absence of Zn(2+), dimers and tetramers are observed. Spectra obtained from solutions of insulin at millimolar concentrations at pH 2.0, conditions under which insulin is known to aggregate in solution, showed signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
241
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(269 citation statements)
references
References 41 publications
22
241
1
Order By: Relevance
“…Following administration, to achieve more efficient absorption into the blood stream, the hexamers are broken down into monomers and dimers, which are prone to fibrillar self-assembly, thus limiting the therapeutic value of this approach. ESI-MS analysis of insulin in the presence of Zn 2ϩ led to the detection of monomers, dimers, tetramers, and hexamers (the latter with two to four Zn 2ϩ ions bound) [55]. The absence of odd-numbered oligomers indicated that such species were not stable entities in solution under these conditions and provided good evidence that the oligomers detected had not been generated artefactually during the ESI-MS process.…”
Section: Are Oligomers Amyloid Intermediates or Dead-end Products Andmentioning
confidence: 97%
See 1 more Smart Citation
“…Following administration, to achieve more efficient absorption into the blood stream, the hexamers are broken down into monomers and dimers, which are prone to fibrillar self-assembly, thus limiting the therapeutic value of this approach. ESI-MS analysis of insulin in the presence of Zn 2ϩ led to the detection of monomers, dimers, tetramers, and hexamers (the latter with two to four Zn 2ϩ ions bound) [55]. The absence of odd-numbered oligomers indicated that such species were not stable entities in solution under these conditions and provided good evidence that the oligomers detected had not been generated artefactually during the ESI-MS process.…”
Section: Are Oligomers Amyloid Intermediates or Dead-end Products Andmentioning
confidence: 97%
“…An early paper reporting the ESI-MS detection of oligomers in protein self-assembly systems focused on insulin, a 51-amino acid residue protein, which forms well-defined oligomers in its native state yet can be induced to aggregate into amyloid fibrils under nonphysiologic conditions [55]. In vivo, insulin is stored in the pancreas as a Zn 2ϩ -containing hexamer composed of three equivalent dimers, and it is this form that is used in the treatment of type 1 diabetes.…”
Section: Are Oligomers Amyloid Intermediates or Dead-end Products Andmentioning
confidence: 99%
“…Their model predicts that macromolecular clusters should form as either thermodynamic or kinetic intermediates. Several authors have presented evidence for such clusters or oligomers for a variety of aggregation-prone IDPs [83][84][85][86][87][88][89][90][91][92]. Sizes of oligomers vary from one system to another and depend on the method of detection and the solution conditions.…”
Section: Implications Of Theoretical Predictions For Kinetics Of Aggrmentioning
confidence: 99%
“…Upon fibrillation, the molecule of insulin undergoes structural changes from a predominantly ␣-helical state to a ␤-sheet rich conformation. The fibrillar ␤-sheets have been described as either parallel (11)(12)(13) or antiparallel (14)(15)(16)). An early model was based on the crystal packing of a despentapeptide insulin molecule (with residues B26-B30 removed) (4,17).…”
mentioning
confidence: 99%